Keeping track of migratory pulmonary lesions. (21st February 2014) - Patrício, Inês Mateus; Caetano, Francisca; Queiró, Joana Carrington; Marado, Daniela
Abstract : Tricuspid valve endocarditis (TVE) is rarely considered in the differential diagnosis of a febrile patient who does not use intravenous drugs.We describe the case of a 62-year-old male patient with a 3-month history of remittent fever and 13% weight loss. The patient denied intravenous drugs use or recent invasive procedures. His medical history included type 2 diabetes, alcohol abuse and smoking. Clinical evaluation revealed systemic inflammatory syndrome with unremarkable physical examination. Ancillary tests showed leucocytosis, thrombocytopenia and elevated C reactive protein. Empiric intravenous ceftriaxone was started, but after an initial improvement, fever relapsed 2 days after stopping antibiotherapy. A CT scan showed multiple disseminated lesions, suggesting lung metastatic tumour. Further studies excluded malignancy and revealed TVE caused by Streptococcus bovis with pulmonary embolism. The aim of our study is to stress the importance of evoking TVE in the differential diagnosis of fever with lung manifestations, and to highlight the possible association between S bovis, colorectal cancer and liver disease.